The study of correlations between Dicranopteris linearis cover area to canopy openness in UiTM Sabah secondary forest / Syadzaratunnuur Aziz - Aziz, Syadzaratunnuur (2014)
UiTM Sabah forest was previously experienced fire in 1996 -1997. A study of correlation between Dicranopteris linearis cover area and canopy openness was conducted in secondary forest in UiTM Sabah from October to November 2014. Data for this study were collected by doing random plot and hemispherical photography at the plot area. 35 quadrates and 10 transects were made with total to 25 random plots. It was obtained that there is positive correlation coefficient, r with r = 0.71. The canopy openness obtained were ranges from 14.07% to 34.10% with mean canopy openness 23.08%. It is highly recommended to include the study of spatial resource availability such as soil pH, nutrients and structure, plants rooting that can change soil structure and influence of allelopathic plants to Dicranopteris linearis.